The carbon diaries 2015 - Lloyd, Saci (Holiday House, 2009)
In 2015, when England becomes the first nation to introduce carbon dioxide rationing in a drastic bid to combat climate change, sixteen-year-old Laura documents the first year of rationing as her family spirals out of control.